#TITLE_ALTERNATIVE# - EKA SYAHPUTRA MAKMUR (NIM 22405009), ERWIN
This research is focused on the development and application of output validation technique and the verification of NCEP/NCAR reanalysis climate model based on wavelet time-frequency analysis. This kind of analysis is expected to be able to give some information about physical process on the assimilation model data which is difficulty obtained through a direct comparation. The benefit is clearly showed on the demonstration of this new technique application on the variable of rainfall observation from 1961 to 2000 time period and NCEP/NCAR model output at 41 locations in Indonesia The method used in this research is wavelet transform which include Continuous Wavelet Transform (CWT), Spectral Analysis, Wavelet Transform Coherence (WTC), RMSE analysis and linier correlation, completed with graphical analysis which can give the information about the identification and the analysis of the scale process from intra seasonal to decade result of the transformation (W[xo(t)] and W[xm(t)]). The analysis is conducted at every station and region and based on the output data of rainfall reanalysis it has showed at certain stations physical process that occur but not the same power. It means that it is still possible for the over estimate or sometimes under estimate occurrence.